Comparison of Cu, Zn and Fe bioleaching from Cu-metallurgical slags in the presence of Pseudomonas fluorescens and Acidithiobacillus thiooxidans. (May 2016) - Potysz, Anna; Lens, Piet N.L.; van de Vossenberg, Jack; Rene, Eldon R.; Grybos, Malgorzata; Guibaud, Gilles; Kierczak, Jakub; van Hullebusch, Eric D.
Abstract: Metal leaching from metallurgical wastes (slags) by means of environmentally friendly approaches is promising for practical applications. The goal of this study was to compare the feasibility of metal bioleaching from Cu slags by means of Pseudomonas fluorescens and Acidithiobacillus thiooxidans . Two size particles (<0.3 mm and 1–2 mm) of two types of Cu slags (massive crystalline slag and granulated amorphous slag) were used to study metal (Cu, Zn and Fe) bioleaching. The 40-days bioleaching experiments with P. fluorescens began at circumneutral pH (7.0), whereas the experiments with A. thiooxidans were started under acidic (pH 2.5) conditions. The results demonstrated that A. thiooxidans catalyzes metal leaching from both slag types investigated. After 21 days of incubation, optimal leaching was achieved and up to 79% Cu, 76% Zn and 45% Fe could be extracted from crystalline slag under conditions of 1 wt.% pulp density and particle size <0.3 mm. The optimal efficiency achieved with amorphous slag was 81% Cu, 79% Zn and 22% Fe when 1% pulp density and 1–2 mm particle size were used. The use of P. fluorescens resulted in poor leaching efficiencies as compared to the performance of A. thiooxidans, presumably due to the higher pH conditions maintained during the P. fluorescens incubations. The maximum metal leaching efficiencies with P. fluorescens were achieved at 1% pulp density and particle size <0.3 mm and did not exceed 10% Cu, 4% Zn, 0.3% Fe for crystalline slag and 4% Cu, 3% Zn, 0.7% Fe for amorphous slag. Both slags exhibited a good potential for bioleaching with A. thiooxidans, however; further optimization of the process parameters ( e.g. pulp density, particle size and pH) is needed to improve the efficiency. Graphical abstract: Highlights: Cu, Zn and Fe were leached from Cu-slags under abiotic and biotic conditions. Acidithiobacillus thiooxidans efficiently improved metal leaching from Cu-slags. Highest metal leaching efficiency was reached for crystalline slag (CS) at 1% pulp density and particle sizes <0.3 mm. Larger fraction sizes (1–2 mm) and lower pulp density (1%) were efficient for amorphous slag (AS).